Synthesis, Characterisation, Theoretical NMR Calculations and Crystal Structure of the 3-methyl-1H-1,2,4?4-triazole-5-amine acetate - Patricia Saraiva Vilas Boas Almeida; José Roberto da Silveira Maia; Márcia Cristina de Souza; Alison Geraldo Pacheco (The Journal of Engineering and Exact Sciences)
The condensation reaction between aminoguanidine bicarbonate with carboxylic acids led to the formation of 3-methyl-1H-1,2,4-triazole-5-amine (mta), 3-methyl-1H-1,2,4l4-triazole-5-amine acetate (Hmta) and 3-phenyl-1H-1,2,4-triazole-5-amine (pta). The compound N-(3-methyl-1H-1,2,4-triazole-5-yl)propan-2-imine (mpta) was obtained by reacting the mta with acetone, upon an attempt of purifying mta in this solvent. The excess of acetic acid obtained the Hmta during the preparation of mta. These compounds were characterised by infrared and multinuclear NMR (1H and 13C) spectroscopy, microanalysis, and melting point. To investigate the formation of possible tautomeric conformations of mta, pta and mpta in solution, a theoretical approach was used to calculate the chemical shifts of carbon 13, based on the values of magnetic shielding tensor (NMR) by MPn and DFT methods. The biological assay of the triazoles mta, pta and mpta against Staphylococcus aureus, Bacillus subtilis, Escherichia coli and Salmonella typhimurium showed no activity at the highest concentration used in the experiment.